Ternary fission induced by polarized neutrons - Gönnenwein Friedrich (EPJ Web of Conferences, 2013)
Ternary fission of (e,e) U- and Pu- isotopes induced by cold polarized neutrons discloses some new facets of the process. In the so-called ROT effect shifts in the angular distributions of ternary particles relative to the fission fragments show up. In the so-called TRI effect an asymmetry in the emission of ternary particles relative to a plane formed by the fragment momentum and the spin of the neutron appear. The two effects are shown to be linked to the components of angular momentum perpendicular and parallel to the fission axis at the saddle point of fission. Based on theoretical models the spectroscopic properties of the collective transitional states at the saddle point are inferred from experiment.